The Fragile Balance of Terror : deterrence in the new nuclear age - Narang, Vipin; Sagan, Scott Douglas (Ithaca and London: Cornell University Press, 2022)
"This volume explores the characteristics and risks in the new nuclear age, which is populated by potentially more nuclear states with less reliable and smaller nuclear arsenals, often best by volatile domestic politics, face more and more intense rivalries, and operate in a novel information environment-a situation we have never previously confronted and which carries heightened risks of advertent and inadvertent nuclear use"--
Includes bibliographical references and index.
Introduction : The Fragile Balance of Terror / Vipin Narang and Scott D. Sagan -- Multipolar Deterrence in the Emerging Nuclear Era / Caitlin Talmadge -- Psychology, Leaders, and New Deterrence Dilemmas / Rose McDermott -- Thermonuclear Twitter? / Vipin Narang and Heather Williams -- Understanding New Nuclear Threats : The Open Source Intelligence Revolution? / Amy Zegart -- How Much Is Enough? Revisiting Nuclear Reliability, Deterrence, and Preventive War / Jeffrey Lewis and Ankit Panda -- Survivability in the "New Era of Counterforce" / Christopher O. Clary -- Command and Control in New Nuclear Powers / David Arceneaux and Peter Feaver -- The Limits of Learning in the New Nuclear Age / Mark S. Bell and Nicholas L. Miller -- Conclusion : The Dangerous Nuclear Future / Vipin Narang and Scott D. Sagan.
Keywords: Deterrence (Strategy); Balance of power; Nuclear weapons -- Political aspects; Security, International